A SYSTEMATIC REVIEW OF GROUP WALKING IN PHYSICALLY HEALTHY PEOPLE TO PROMOTE PHYSICAL ACTIVITY. (17th January 2018) - Meads, Catherine; Exley, Josephine
Abstract : Background: Walking is a good way to meet physical activity guidelines. We examined the effectiveness of walking in groups compared with walking alone or inactive controls in physically healthy adults on physical activity and quality of life. (PROSPERO CRD42016033752). Methods: We searched Medline, Embase, Cinahl, Web of Knowledge Science Citation Index, and Cochrane CENTRAL until March 2016, for any comparative studies, in physically healthy adults, of walking in groups compared with inactive controls or walking alone, reporting any measure of physical activity. We searched references from recent relevant systematic reviews. Two reviewers checked study eligibility and independently extracted data. Disagreements were resolved through discussion. Quality was assessed using likelihood of selection, performance, attrition, and detection biases. Meta-analysis was conducted using Review Manager 5.3. Results: From 1, 404 citations, 18 studies were included in qualitative synthesis and 10 in meta-analyses. Fourteen compared group walking to inactive controls and four to walking alone. Eight reported more than one measure of physical activity, none reported according to current guidelines. Group walking compared with inactive controls increased follow-up physical activity (9 randomized controlled trials, standardized mean difference [SMD] 0.58 [95 percent confidence interval CI, 0.34–0.82] to SMD 0.43 [95 percent CI, 0.20–0.66]). Compared with walking alone, studies were too few and too heterogeneous to conduct meta-analysis, but the trend was improved physical activity at follow-up for group walking participants. Seven (all inactive control) reported quality-of-life: five showed statistically significantly improved scores. Discussion: Better evidence may encourage government policy to promote walking in groups. Standardized physical activity outcomes need to be reported in research.